Identifying in-market application of Pelargonium root extract EPs 7630 for the treatment of COVID-19: analysis of pharmacovigilance data - Malek, Fathi Abdul; Funk, Petra (Frontiers in Pharmacology, 2024)
Phytopharmaceutical products are successfully used for acute respiratory infections and may therefore be promising candidates for adjuvant symptomatic treatment of COVID-19.In vitro and clinical studies suggest that the proprietary Pelargonium sidoides DC. root extract EPs 7630, has antiviral and immunomodulatory properties, and effects on SARS-CoV-2 propagation have been shown in vitro. Medicinal products containing the extract have been approved for the symptomatic treatment of acute viral respiratory tract infections. We present a retrospective review of case reports submitted spontaneously to the pharmacovigilance database of the manufacturer of EPs 7630 and containing information on the off-label use of the extract for the treatment and prophylaxis of COVID-19 and of post-COVID-19 syndrome. Eligible case reports were identified by automated database searches.Forty-four case reports filed between December 2019 and February 2023 were eligible for analysis. More than ¾ described the use of EPs 7630 for treatment of COVID-19 while the remaining reports referred to the treatment of post-COVID-19 syndrome or on COVID-19 prophylaxis. 15/22 cases which reported on treatment duration indicated an intake of EPs 7630 for up to seven days. Five case reports indicated the use of EPs 7630 as COVID-19 monotherapy while 14 indicated a combination treatment with other drugs. All 28 cases that reported on treatment outcome characterized the patients as improved. Thirty case reports (68%) did not indicate any complications. The most frequent suspected adverse reactions were gastrointestinal complaints and hypersensitivity reactions, both of which may occur as known adverse effects of EPs 7630. No unexpected adverse reactions were observed.Reported cases confirm that there was a certain off-label use of EPs 7630 for COVID-19 in the market. Even though no formal conclusions about the efficacy of EPs 7630 in COVID-19 can be drawn, a beneficial effect would be explainable by the pharmacological profile of the extract. Further assessment of the effects of EPs 7630 in COVID-19-related indications therefore appears to be both justified and promising, particularly as the available case reports did not give rise to any safety concerns also in this patient group.